METODE PENENTUAN AWAL BULAN RAMADAN, SYAWAL, DAN ZULHIJJAH MENURUT DEWAN DAKWAH ISLAMIYAH INDONESIA - Abshor, Muhammad Ulil (UIN Sunan Kalijaga Yogyakarta, 2017)
Dewan Dakwah Islamiyah Indonesia (DDII) when setting the start of Ramadan and Syawal they follow the Indonesian government method (imkanur rukyah) with matla 'Indonesia (wilayatul hukmi, parts of Indonesia as a jurisdiction), but when the month of Idul Adha following the government's decision of Saudi Arabia. The reason, Eid al-Adha is closely related to the standing events so that decisions regarding the events wukuf the government authorities Saudi Arabia. Rukyah sect DDII is Mecca referring Rukyah official letter signed by the Secretary General of the Muslim World League Syeikh Muhammad Shalih Islami Qazzaz Number: 1/6/5/45 dated July 25th 1975 regarding determination of Eid Al Adha addressed to the members of the Majlis Mohammad Natsir as Ta ' The Mudir side of Maktab and the General Counsel of Rabithah 'Alam Islam. In the letter mentioned proposition Syeikhul Azhar Abdul Halim Mahmud in the form of a press release in 1975 that called for that in terms of determining the beginning of the month of Zulhijjah, should all be guided by the results of an Islamic state Rukyah Saudi Arabia, so that the Muslims of the opinion in the issue of the establishment of the standing at Arafat. DDII use understanding the verses of the Quran and hadith, related to the argument of the testimony rukyah, replenish a fair witness to determine the beginning of fasting, while the end of the fasting decided to use at least two witnesses were fair and tsiqah (reliable). Witnesses are not required to be male or female, because what is delivered is a news of observation.